Easy to Snack—Hard to Digest? Strategies of Dis/Array in Streaming, Social Media, and Television - Kim Carina Hebben; Christine Piepiorka (Media and Communication)
In the digital age, the television landscape is profoundly expanded and dispersed across multiple media, introducing new paradigms of (post-)televisuality shaped by its constant digital transformation. Television content is distributed across digital platforms that fundamentally change its consumption practices. Through its fragmentation and digitization, television is breaking down into snippets—short, engaging pieces of media—that provide a dynamic, customizable, and “snackable” viewing experience, so that it is supposedly easy to digest. As a result, not only is there a shift in how content is viewed, but there is also a shift in how content is produced. Social media platforms and their algorithms have emerged as central to this transformation, facilitating the dissemination and discovery of television content in unprecedented ways. Platforms like Instagram and TikTok are not just venues for discussion and sharing but are also directly influencing the digital transformation of television. While specific essential characteristics define television (such as its seriality, scheduling, or formats), the digital transformation emerging from the internet is disrupting the medium and requiring (or even demanding) participatory modifications based on experimenting with different forms of media so that television gets expanded, explored, manipulated, and played with by consuming snackable content bit by bit. The concept of dis/array proposed in this article encapsulates the dual forces of fragmentation and reorganization. Disarray, characterized by the oversupply of content, reflects the challenges audiences face in navigating a dispersed landscape. Conversely, array represents the efforts by platforms and users to restore order through algorithms, categorization, and interactive engagement. By analyzing current trends and audience behaviors, this article reveals how streaming, social media, and snippets contribute to the transformation of television.